2000
DOI: 10.1093/jnci/92.4.328
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hormone Replacement Therapy on Breast Cancer Risk: Estrogen Versus Estrogen Plus Progestin

Abstract: This study provides strong evidence that the addition of a progestin to HRT enhances markedly the risk of breast cancer relative to estrogen use alone. These findings have important implications for the risk-benefit equation for HRT in women using CHRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
287
5
20

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 791 publications
(330 citation statements)
references
References 0 publications
18
287
5
20
Order By: Relevance
“…Early menarche and late menopause increase breast cancer risk, as they prolong exposure to oestrogen and progesterone. [13][14][15][16][17][18][19][20][21][22] Long-term combined hormone replacement therapy (HRT) treatment (> 5 years) after the menopause is associated with a significant increase in risk. However, shorter-term treatments may still be associated with risk to those with a family history of breast cancer.…”
Section: Hormonal and Reproductive Risk Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Early menarche and late menopause increase breast cancer risk, as they prolong exposure to oestrogen and progesterone. [13][14][15][16][17][18][19][20][21][22] Long-term combined hormone replacement therapy (HRT) treatment (> 5 years) after the menopause is associated with a significant increase in risk. However, shorter-term treatments may still be associated with risk to those with a family history of breast cancer.…”
Section: Hormonal and Reproductive Risk Factorsmentioning
confidence: 99%
“…15 Oestrogen-only HRT has a risk that appears much lower, and it may be risk neutral. [16][17][18][19] A meta-analysis also suggested that both during current use of the combined oral contraceptive and 10 years post use, there may be a 24% increase in risk of breast cancer. 13 A woman's age at first pregnancy influences the relative risk (RR) of breast cancer, as pregnancy transforms breast parenchymal cells into a more stable state, potentially resulting in less proliferation in the second half of the menstrual cycle.…”
Section: Hormonal and Reproductive Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…About 65% of estrogen positive breast cancers are also progesterone receptors positive, which means that progesterone may turn on breast cancer cell growth [14]. However, progesterone proliferative effects on mammary gland development and tumor genesis are not well recognized [15][16][17].…”
mentioning
confidence: 99%